Extraction of clouds from satellite imagery in the Antarctic (abstract) - Suzuki, Kazuya; Yoshino, Takeo; Yamanouchi, Takashi; Kawaguchi, Sadao; Tanaka, Shinya (1985)
P(論文) departmental bulletin paper